Expression of the cytolethal distending toxin in a geographically diverse collection of Haemophilus ducreyi clinical isolates. Issue 4 (5th August 2003) - Kulkarni, K; Lewis, D A; Ison, C A
Abstract : Objective: To screen a collection of isolates of Haemophilus ducreyi for expression of the cytolethal distending toxin (CDT). Methods: 45 clinical isolates of H ducreyi were screened for cytotoxic activity by examining the effect of culture supernatants on Hela cells. Expression was confirmed using immunoblotting with CDT specific monoclonal antibodies and the presence of the cdt genes determined by amplification of the cdt genes in a multiplex polymerase chain assay. Results: Of the 45 clinical isolates, six isolates from differing geographical origins did not demonstrate cytotoxic activity. Expression of CDT was also not detected in these six isolates using immunoblotting and the genes cdtA, cdtB, and cdtC were not amplified using PCR. The remaining isolates demonstrated cytotoxic activity, expressed the CDT proteins, and the presence of the cdt genes was confirmed. Conclusions: CDT is considered a virulence factor of H ducreyi but was found to be absent in 13% of isolates from different geographical origins.